KUALITAS PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH KEBUMEN (Studi Kasus: Pelayanan Rawat Inap) - , OVIA AFITRI, Dr. Ely Susanto, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public service is issue impotant for topic. Because public service is communication government with society. Society hope the government make deccision public service good for socciety. Public service healthy is hospital. Hospital at regency is Kebumen Hospital. Kebumen Hospital is hospital in regency Kebumen then society complain service Kebumen hospital. Employee competence is low make the society complain. Facilities is little so make society many complain. Suggestion for Kebumen hospital from researcher is for plus many facilities, and groeth employe competence for good.